2005
DOI: 10.1074/jbc.m410483200
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Analyses of a Phe/Tyr Switch Controlling Product Specificity of Histone Lysine Methyltransferases

Abstract: The functional significance of mono-, di-, and trimethylation of lysine residues within histone proteins is under investigation. Evidence from several model organisms suggests that different methylated states of H3 Lys 9 (H3K9) are generated by specific histone methyltransferases (MTases) to mark distinct types of silent chromatin. Sequence alignment of all histone lysine MTases with known product specificity suggested that a key residue in the active site determines how many methyl groups they add. We examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
169
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(198 citation statements)
references
References 45 publications
22
169
0
2
Order By: Relevance
“…Elegant mutagenesis studies have shown that mutagenesis of DIM5 F281 to Y converts the enzyme to a monomethyltransferase, whereas the reciprocal mutation in SET7/9 (Y305 to F) creates an enzyme capable of trimethylating its substrate [23]. More generally speaking, it seems that the aromatic determinant (Y or F) is a mechanism widely employed by SET domain-containing HKMTs to control the degree of methylation [24,25].…”
Section: Lysine Methylationmentioning
confidence: 99%
“…Elegant mutagenesis studies have shown that mutagenesis of DIM5 F281 to Y converts the enzyme to a monomethyltransferase, whereas the reciprocal mutation in SET7/9 (Y305 to F) creates an enzyme capable of trimethylating its substrate [23]. More generally speaking, it seems that the aromatic determinant (Y or F) is a mechanism widely employed by SET domain-containing HKMTs to control the degree of methylation [24,25].…”
Section: Lysine Methylationmentioning
confidence: 99%
“…In vitro G9a generates mainly H3K9me1 and H3K9me2 (ref. 8), as well as H3K9me3 after long incubation 9 . In contrast to the Dim-5 and Suv39H1 H3K9 methyltransferases, G9a methylates not only H3K9 but also H3K27 (ref.…”
mentioning
confidence: 99%
“…The mutation did not affect the catalytic activity of G9a; however, the reaction by F1205Y stalled at the monomethyl stage [56]. Thus, the F1205Y mutation changed the product specificity of G9a from a fast mono/di-MTase with a slow tri-MTase activity to a predominantly mono-MTase without affecting overall catalytic activity, analogous to the F281Y mutation for DIM-5.…”
Section: A Tyrosine/phenylalanine Switch Controls Product Specificitymentioning
confidence: 89%
“…Sequence alignment including HKMTs with known product specificity suggests that the tyrosine/phenlyalanine switch rule may be generalized (see Table 1 of reference [56]). Both Arabidopsis KYP and SUVH6 have a tyrosine at the switch position and are primarily monoMTases [57].…”
Section: A Tyrosine/phenylalanine Switch Controls Product Specificitymentioning
confidence: 99%